A world made of knowledge : pathways into the knowledge society - Stehr, Nico, 1942-; Ruser, Alexander (World Scientific, 2025)
More than three decades after Gernot Böhme and Nico Stehr began to explore modern "knowledge societies", the concept has transformed sociological inquiry into the dynamics of contemporary society. But even a quick internet search shows that the term is not only limited to academic circles. Moreover, international bodies such as the Organisation for Economic Co-operation and Development (OECD) underline the importance of transformative processes toward knowledge societies for global tertiary education and promote "inclusive knowledge societies for sustainable development". This book brings together Nico Stehr's key writings on the knowledge society and serves as an authoritative resource for students, scholars, and professionals. Previously published articles and chapters have been carefully selected to take the reader from the formulation and refinement of the concept to scholarly contributions that test its applicability and explanatory power in empirical case studies. In addition, the volume includes new and original material by Nico Stehr that will help the next generation of scholars explore novel and pressing issues such as the role of digital technologies and AI in modern knowledge societies and future inequalities in knowledge capitalism.